2008
DOI: 10.1002/pbc.21632
|View full text |Cite
|
Sign up to set email alerts
|

Extra‐renal non‐cerebral rhabdoid tumours

Abstract: ERRTs share the same chemosensitivity, early recurrence, and poor prognosis as renal and cerebral RTs. No chemotherapy regimen demonstrates a superior response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
2
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 51 publications
0
57
2
5
Order By: Relevance
“…At 6 months a PET scan was performed and the patient had no evidence of disease. [5,6,[10][11][12][13][14][15][16][17][18][19][20][21]. In a review of the English literature, 14 cases of primary MRT involving the soft tissues of the head and neck were identified [11][12][13][14][15][16][17][18][19][20][21] (Table 1).…”
Section: Case Reportmentioning
confidence: 99%
See 4 more Smart Citations
“…At 6 months a PET scan was performed and the patient had no evidence of disease. [5,6,[10][11][12][13][14][15][16][17][18][19][20][21]. In a review of the English literature, 14 cases of primary MRT involving the soft tissues of the head and neck were identified [11][12][13][14][15][16][17][18][19][20][21] (Table 1).…”
Section: Case Reportmentioning
confidence: 99%
“…One study by Sultan et al [10] found that radiation therapy, age at diagnosis (with children under 2 showing the worst prognosis) and tumor stage to be the most significant prognostic factors. Reports of overall survival rates of patients with MRT range from 20 to 33 % [5,10]. Distant metastasis has been reported and is more common in renal MRT [5,10].…”
Section: Case Reportmentioning
confidence: 99%
See 3 more Smart Citations